DEVELOPMENT OF E-TIBI+ AS EARLY DETECTION AND SYSTEMATIC MANAGEMENT OF TUBERCULOSIS CASES IN PLHIV - Erwin Astha Triyono; Feriawan Tan; Lilis Masyfufah; Sulvy Dwi Anggraini; Maria Lucia Inge Lucida; Soedarsono; Merita Arini; Tri Pudy Asmarawati; Ariani Permatasari; Rosita Dwi Yuliandari (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: HIV and TBC combinations have received global public attention in recent years. Current collaborative tuberculosis and HIV elimination strategy is not enough to eradicate these two infectious diseases. Therefore, an innovative elimination approach leveraging advancements in digital technology is urgently needed. Purpose: To evaluate the tuberculosis elimination by optimizing case finding and monitoring treatment completion through the Early Detection and Management of Tuberculosis Application System + (E-TIBI+) application based on self-assessment in the HIV population. Method: This observational cohort study was conducted in Surabaya city, East Java Province, Indonesia in the period of September - October 2024. The study population consisted of adult PLHIV who completed the E-TIBI+ self-assessment. The E-TIBI+ application is a web-based platform. Data analysis included univariate analysis in the form of frequencies for each variable and crosstab analysis with the Kendall tau-b test in E-TIBI+ application acceptance data. Result: From a total of 386 patients screened, 61 (15.80%) PLHIV were suspected of having TBC. From the 61 patients, there were 17 patients who sought diagnosis at the health facility of their choice. User acceptance of the E-TIBI+ application by PLHIV patients tends to be positive and statistically significant. Conclusion: The E-TIBI+ application demonstrates strong potential to enhance early detection and systematic monitoring of tuberculosis case management among PLHIV through digital technology.